Pengaruh Kualitas Pelayanan dan Suasana Toko terhadap Kepuasan Pelanggan melalui Keputusan Pembelian di Kopi Nako Ciracas - Ika Rahmawati; Rivera Pantro Sukma Silitonga (Human Capital Development, 2023)
This study aims to determine the effect of service quality and store atmosphere on customer satisfaction through purchasing decisions at Kopi Nako Ciracas. The sampling technique used a purposive sampling method of 200 respondents and the data was analyzed using Structural Equation Modeling (SEM) through PLS version 3.0. The results of this study are service quality has no effect on customer satisfaction, service quality affects purchasing decisions, store atmosphere affects customer satisfaction and purchasing decisions, but service quality and store atmosphere have an indirect effect on customer satisfaction through purchasing decisions.